Metacognition in Academic Writing: Analyzing Strategies and Gender Differences among Moroccan University EFL Learners - EL Hosayny, Otmane; Razkane, Hassane; Yeou, Mohamed (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
Metacognitive awareness plays a facilitative role for students to regulate, monitor, and evaluate their cognitive processes. While plethora of studies has been conducted in L2 writing context, yet little research has delved into the interconnectedness between metacognitive strategy use, gender as mediating factor, and writing performance in English as a Third language (L3) context. To fill this research gap, the present study tackled the relationship between students’ awareness of metacognitive writing strategies and argumentative writing performance. It also sought to determine the role of gender in moderating this relationship. Using convenience sampling, eighty-two second-year university students were assigned an argumentative essay test and were administered an adapted version of a questionnaire to measure their awareness of metacognitive writing strategies during the writing process. Data were analyzed using various statistical tools, including multiple linear regression and ANCOVA analyses. Results indicated that although students demonstrating moderate levels of awareness of metacognitive writing strategies, this awareness did not strongly correlate (r=0.192) with their academic writing performance. Despite students’ awareness of metacognitive strategies, they still lacked active implementation of these strategies. Gender analysis revealed the existence of slight gender differences in metacognitive awareness of writing strategies and writing outcomes, with females slightly outscoring their male counterparts on both metacognitive and writing achievement. To this end, we recommend implementing targeted explicit instruction and scaffolded support to aid students in applying these strategies effectively in their academic writing tasks. By fostering metacognitive awareness and emphasizing ongoing practice, students cannot only translate their metacognitive awareness into improved performance but also acquire the essential tools for academic success.